Alternative Splicing of the Pituitary Adenylate Cyclase-Activating Polypeptide Receptor PAC1: Mechanisms of Fine Tuning of Brain Activity - Blechman, Janna; Levkowitz, Gil (Frontiers in Endocrinology, 2013)
Alternative splicing of the precursor mRNA encoding for the neuropeptide receptor PAC1/ADCYAP1R1 generates multiple protein products that exhibit pleiotropic activities. Recent studies in mammals and zebrafish have implicated some of these splice isoforms in control of both cellular and body homeostasis. Here, we review the regulation of PAC1 splice variants and their underlying signal transduction and physiological processes in the nervous system.